2016
DOI: 10.18632/oncotarget.8689
|View full text |Cite
|
Sign up to set email alerts
|

The toxic effects and possible mechanisms of Bisphenol A on oocyte maturation of porcine in vitro

Abstract: Bisphenol A (BPA) and Di-(2-ethylhexyl) phthalate (DEHP) are widely used in the plastic industry such as water bottles, containers, packaging and toys. BPA and DEHP are shown to be the endocrine disruptors which disturb the endocrine system and are linked to several diseases including infertility. In this study, we investigated the effects of BPA exposure on porcine oocyte maturation and its possible reasons. Our results showed that: (i) the rates of oocyte maturation significantly decreased with 250 μM BPA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 43 publications
7
50
1
7
Order By: Relevance
“…This study also provides a warning for women who are frequently exposed to IBP at high concentrations by using in vitro culture model of porcine cumulus oocyte complexes as can be seen in Figure . The reason we chose porcine oocytes as a model because oocyte size and maturation time are more like human than mouse (Santos et al ), and several articles have used porcine cumulus oocyte complexes to evaluate oocyte (Liu et al ; Han et al ; Wang et al ; Miao et al ; Liang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also provides a warning for women who are frequently exposed to IBP at high concentrations by using in vitro culture model of porcine cumulus oocyte complexes as can be seen in Figure . The reason we chose porcine oocytes as a model because oocyte size and maturation time are more like human than mouse (Santos et al ), and several articles have used porcine cumulus oocyte complexes to evaluate oocyte (Liu et al ; Han et al ; Wang et al ; Miao et al ; Liang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…7 Conversely, in another previous study, we observed no global methylation changes after 48 h exposure to BPA, whereas significant increase were shown on global level of 5-mC% (1.3 fold) after 10 μM of BPA for 96 h exposure in neuroblastoma (SHSY-5Y) cells. 9 According to results of this study, it has been shown that BPA caused global hypomethylation in rat liver 24 , human fetal liver samples 25 , and porcine oocyte culture at 250 μM of concentration 26 .…”
Section: Resultsmentioning
confidence: 77%
“…While the exposure of somatic cells creates health problems for exposed individuals, influence on gametes leads to an intergenerational effect when the burden is transduced to the next generation of daughters and sons [81]. Indeed, the exposure to bisphenols impairs genome-wide DNA methylation, as well as histone code in oocytes [71,82], followed by changes in the imprinting of genes in the embryo and placenta [83]. In spermatozoa, DNA methylation [84] is potentially affected by environmental pollutants, leading to aberrant gene imprinting [85,86].…”
Section: Molecular Mechanism Of Eds In Extremely Low Dosesmentioning
confidence: 99%